Teachers’ Written Feedback on Digital Answer Scripts during COVID-19: Views, Preferences, and Expectations of the EFL Students - Md. Zohorul Islam (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
This study aimed at exploring Bangladeshi students’ views, preferences and suggestions regarding teacher’s feedback on the digital examination scripts during the COVID-19 pandemic. It followed the quantitative method of research to check the views, preferences and expectations of the students on feedback on the digital answer scripts provided by the teachers. Purposive sampling was used in the present study. The sample consisted of 115 undergraduate students at the Department of English, Green University of Bangladesh, Bangladesh. The obtained data was quantified and analyzed using Microsoft Excel. The findings revealed that students acknowledged the importance of feedback in the digital answer scripts and prefer both negative and positive feedback from the teacher. The findings also show that the students expect corrective feedback based on the grammar and language errors in the answer scripts. However, the results revealed that a portion of the students focuses only on the score they receive and not on the feedback. Based on the findings, the study implies that the teachers should explore the students’ views regarding specific types of feedback and develop a method to provide comments that attract the students to go through all the comments and reflect for future improvements.